Mapping the evolution of platform society : multidisciplinary insights from social and political sciences - Goglio, Valentina; Biancalana, Cecilia (Emerald Publishing Limited, 2025)
Our society is becoming inextricably intertwined with digital platforms. Mapping the Evolution of Platform Society brings together a team of multidisciplinary scholars to investigate the intricate web of challenges and opportunities posed by the digital landscape. The chapters provide novel research on the impact of platforms on education, media, politics and social disadvantage. Delivering a necessary update to seminal work with new empirical evidence and evolving key challenges - such as the role of TikTok - the authors do not merely identify risks of the 'platformization' of society, they offer a vital exploration of potential solutions and best practices. Opening with an introduction by the editors, it then covers five sections exploring education and lifelong learning, discrimination and marginalized communities, media and news dissemination, the digital transformation of government, and the environmental challenges of the platform society. Encompassing case studies and analyses from countries and regions often overlooked in existing literature, this collection offers a global perspective on the evolution of the opportunities and inherent challenges posed by the platform society. Emerging from genuine interdisciplinarity, deriving from rigorous research across education, social work, journalism, government, and environmental studies, this is rich reading for scholars from across the political and social sciences interested in the risks and opportunities of this evolving societal trend.